International relations - Goldstein, Joshua S.; Pevehouse, Jon C. (Longman Pearson Education, 2011)
Thoroughly updated to cover world affairs through 2009, the brief version of International Relations presents the same approach and coverage as the bestselling comprehensive survey but in a streamlined and flexible format. From war and trade to human rights and the environment, this text is praised for being the most current introduction to international relations theory as well as security, economic, and global issues. Applying a broad range of theoretical perspectives to help students analyze what is happening in the world today, International Relations, Brief Edition is perfect for courses where multiple texts are assigned.